Prevalence, incidence and risk factors of tamoxifen‐related non‐alcoholic fatty liver disease: A systematic review and meta‐analysis - Lee, Bora; Jung, Eun‐Ae; Yoo, Jeong‐Ju; Kim, Sang Gyune; Lee, Cheon‐Beom; Kim, Young Seok; Jeong, Soung Won; Jang, Jae Young; Lee, Sae Hwan; Kim, Hong Soo; Jun, Baek Gyu; Kim, Young Don; et al. (Liver international, 2020)
Background & Aims Tamoxifen is associated with an increased risk of developing fatty liver. The aim of this systematic review and meta‐analysis was to evaluate the prevalence and incidence of fatty liver developed after tamoxifen treatment in breast cancer patients. Methods A systematic search of PubMed (Medline), EMBASE, OVID Medline, the Cochrane Library and other databases was performed for this review. The s obtained from the search were reviewed by two investigators who chose manuscripts for full‐text review. The event rates were calculated with a random‐effects model and quality‐effects model. Results The search yielded 165 references. Of these, 24 were included in the quantitative summary. We analysed the data of a total of 6,962 patients treated with tamoxifen and 975 patients not treated with tamoxifen. The prevalence of fatty liver among patients with breast cancer taking tamoxifen was 40.25 per 100 patients and the incidence rate was 12.37 per 100 person‐years. The incidence of fatty liver was much higher in the tamoxifen group than in the control group [incidence rate ratio: 3.12, 95% CI (confidence interval): 2.05‐4.75, I2 = 61%], regardless of region. The main risk factors were body mass index (BMI) [hazard ratio (HR): 1.15, 95% CI: 1.09‐1.22] and hypercholesterolaemia (HR: 1.01, 95% CI: 1.00‐1.02). Conclusion The use of tamoxifen was associated with increased risks in the incidence and prevalence of fatty liver, especially in patients with high BMI and hypercholesterolaemia.